Multidiciplinary Review on The Effects of Backdoor Listing Action Against Standby Purchaser (Acquisitor Company) - Adityadarma Bagus Priasmoro Suryono Putro; Budi Santoso; Rachmi Sulistyarini (Jurnal Dinamika Hukum, 2020)
Backdoor Listing is a "Corporate Action" taken often by companies in Indonesia today. Backdoor Listing is an act in which a closed limited liability company acquires an open limited liability company in order to conduct a right issue without going through the Initial Public Offering (IPO) process. In this paper, the writers attempt to discuss the legal consequences of Backdoor Listing action against Standby Purchasers. The research method was normative juridical using statutory approach and concept approach. In the discussion section, first the writers described the IPO and its inhibition in terms of legal and economic point of view. The review then led to the use of Backdoor Listing as an alternative to capital expansion in addition to the IPO path. The writers inventoried the requirements that must be met before backdoor listing as a conditional legal action.Keywords: initial public offering; backdoor listing; backdoor listing requirement; standby purchaser.